Knowledge, attitudes and practices on sunscreen usage in preventing skin cancer among university students - Nurul Farhana Jufri,; Nur Zakiah Mohd Saat,; Suganya Muthaya,; Muhammad Syahmi Alias,; Nur Mashitah Aiham,; Siti Norbaya Tajuddin,; Nurul Syahindah Mohd Fahrizuddin,; Nurkhalida Athirah Khaidir,; Lee, Chia-I; Noor Azlinda Ali,; Ummu Asma’ Hakimah Hisamudin,; Nur Sabrina Merasa,; et al. (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2021)
Solar ultraviolet radiation is one of predisposing risk factors for skin cancer. The use of sunscreen plays a vital role in the prevention of skin cancer. A cross-sectional study was conducted to evaluate the knowledge, attitudes and practices related to sunscreen use in the prevention of skin cancer among undergraduate students of Universiti Kebangsaan Malaysia (n=78) in the Faculty of Health Sciences (FSK), Faculty of Engineering and Built Environment (FKAB) and Faculty of Social Sciences & Humanity (FSSK). Majority of the students used sunscreen. The mean level of knowledge for FSSK students was the highest compared to FSK and FKAB students. Next, the mean level of attitude for FSSK students was higher than the FSK and FKAB students. Meanwhile, there was a significant difference (p<0.05) in attitude between FSSK and FKAB students. FSSK students demonstrated highest mean level of practice compared to FSK and FKAB students. Finally, FKAB recorded the lowest number of students with high knowledge and the usage of sunscreen with statistical significance (p<0.05) between the level of knowledge and the use of sunscreen. This indicates that there was a linear association between level of knowledge and the use of sunscreen among FKAB students. In conclusion, knowledge, attitudes and practice were generally satisfactory among UKM students. However, periodic awareness could be applied to instill a healthy habit of using sunscreen in future.